2021
DOI: 10.3390/jcm10194492
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Its Associations with Organ Complications in Adults after Fontan Operation

Abstract: Reduction of heart rate variability (HRV) parameters may be a risk factor and precede the occurrence of arrhythmias or the development of heart failure and complications in people with postinfarct left ventricular dysfunction and after coronary artery bypass grafting. Data on this issue in adults after a Fontan operation (FO) are scarce. This study assessed the association between HRV, exercise capacity, and multiorgan complications in adults after FO. Data were obtained from 30 FO patients (mean age 24 ± 5.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…There is increasing interest in the use of markers and risk scores as well as in testing their clinical applicability in cardiovascular medicine [25][26][27][28][29][30][31][32][33]. Several factors have been found to be associated with LVH assessed by different modalities [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing interest in the use of markers and risk scores as well as in testing their clinical applicability in cardiovascular medicine [25][26][27][28][29][30][31][32][33]. Several factors have been found to be associated with LVH assessed by different modalities [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the findings by Claessen et al and Hedlund et al, who also demonstrated regular HR response and speculated that reduced HR peak in Fontan patients might be an expression of a physiological reaction to maintain SV and Qc within the context of Frank–Starling mechanism, because of reduced preload ( 35 , 36 ). In addition, due to the numerous operations, many Fontan patients have a lack of responsiveness to modulation by the autonomic nervous system and an impaired sinus node function, both with the consequence of a limited HR variability and HR reserve ( 13 , 37 , 38 ). Here, similar to previous studies, Fontan patients showed significantly lower HR peak compared to controls, but these values were measured at significant lower P peak ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients after FO, electrodes are located on the epicardium. Thus, every single decision regarding implantation, particularly in the case of young patients, should be made with caution, taking into account the possible complications in follow-up observation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%